Defensive reactions of apple cultivars Angold and HL 1834 after fungal infection - J. Schovánková; H. Opatová (Horticultural Science, 2011)
Apple cultivars (Malus domestica Borkh.) were inoculated with a significant apple fruit fungal pathogen, Monilinia fructigena Honey ex Whetzel. Defensive reactions, especially enzyme activity and production of phenolic compounds, were compared. Changes of phenolic content and activity of phenylalanine-ammonia lyase (PAL) were determined 7, 14 and 21 days after the inoculation. Progress of rotting was similar for both cultivars at first but defensive reactions were different. The increase of phenolic compounds was observed; their concentration and composition were influenced by location in the fruit. A very good correlation was found between the activity of phenylalanine-ammonia lyase and total phenolic content.